Pemberdayaan Kader Kesehatan melalui Pembentukan Kelompok “Mapia” Mahir Pijat Bayi disertai Murottal untuk Mengoptimalkan Perkembangan Bayi di Desa Bambu, Mamuju, Sulawesi Barat - Supratti; Andi Nasir; Syamsidar; Iswan HR; Zauqiah Putri Ramadhani; Nur Adillah (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Baby massage offers significant benefits, such as strengthening the bond between mother and child, improving weight gain, and optimizing the baby’s development. The goal of this community service activity is to enhance the knowledge and skills of health cadres through the "MAPIA" (Mahir Pijat Bayi - Expert Baby Massage) group, accompanied by murottal, to support infant development. This activity is carried out in Bambu Village, under the jurisdiction of the Bambu Public Health Center, from March to October 2024. The method used includes education and training for the community. The results show that health cadres were able to demonstrate baby massage techniques according to the provided module. The follow-up plan involves training mothers in the community on baby massage, with guidance from the cadres. Although some families initially resisted, after receiving an explanation about the benefits of baby massage, they agreed to participate. Furthermore, health cadres successfully used the Developmental Screening Questionnaire to assess the babies’ growth according to their age. The results indicated that 100% of the babies observed showed age-appropriate development. This activity successfully optimized the role of health cadres in supporting infant development within the community.